Barriers to the adoption of multiple agricultural innovations: Insights from Bt cotton, wheat seeds, herbicides and no-tillage in Pakistan - Muhammad Bilal; Tinoush Jamali Jaghdani (International Journal of Agricultural Sustainability, 2024)
The slow pace of the adoption of the latest innovations in agricultural technology innovations impedes sustainable farming practices and sustainable agriculture in developing countries. This study investigates the potential reasons that stop smallholder farming households from adopting genetically engineered seeds (Bt cotton and improved wheat seeds), herbicides resulting from cutting-edge technologies, and no-tillage farming. Utilizing original farm household-level data from 275 smallholder farming households in Pakistan, we employ multivariate probit models. The results show that the adoption of innovative technologies is not an isolated, separate process but a concoction of available technologies and cropping patterns. The estimates of the multivariate probit models show that farm machinery index, off-farm income sources, and farmers' education facilitate technology adoption. The observations and estimates indicate that a lack of agricultural extension service contacts is present, which slows down the farmers' adoption of agricultural technological inputs. Therefore, promoting the role of agricultural extension services (qualitatively and quantitatively) is likely to play a role in multiple technology adoption. Furthermore, the significant effect of off-farm employment shows that the lack of financial resources is another factor slowing the adoption of innovative technologies, which depends on liquidity for necessary expenditures.
Keywords: 630; agricultural extension; cotton-wheat zone; cutting-edge technology; off-farm income sources; smallholder farming households